Influence of Work Ethos, Communication, and Work Motivation on the Work Discipline of Employees in the Traffic Division of the Ngawi Regency Transportation Department - Aan Wahyudi; Ahadiati Rohmatiah; Hartirini Warnaningtyas (International Journal of Business and Quality Research, 2026)
The success of public sector organizations is heavily dependent on human resources, where employee work discipline serves as a core indicator of professionalism and service quality. This study aims to analyze the influence of work ethos, communication, and work motivation on employee work discipline within the Traffic Division of the Ngawi Regency Transportation Department. Pre-research observations indicated various discipline challenges, including tardiness, suboptimal field performance, and coordination gaps. Through rigorous paraphrasing of academic literature, this study establishes that work ethos reflects an individual's ethical commitment, organizational communication acts as the medium for operational alignment, and motivation provides the behavioral drive necessary to achieve performance standards. The results of this study are expected to offer strategic insights for regional governments in enhancing bureaucratic performance and public service delivery.